Dochodzenie roszczeń wynikających z przewlekle prowadzonego postępowania sądowego - Ciućkowska, Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This paper deals with the issues related to the lenght of court proceedings and chronicity of litigations. It concernes constitutional and conventional regulations related to the right to the court and the right to a fair trail, from which follows the right to reasonable time of litigation. Also problems conected to compensation for pecuniary and non-pecuniary damages arrising from chronicity of litigation found their reflections in this article.